The Effect Self-Efficacy and Self-Confidence on Academic Anxiety, with Extrinsic Motivation as a Mediating Variabel - Fitria Yuningsih; Muniro Tujduja; Anin Deviani; Onwardono Rit Riyanto (Kirana Publisher (KNPub), 2026)
This study examines the influence of self-efficacy and self-confidence on students' learning anxiety, with extrinsic motivation acting as a mediating variable among elementary school students. A quantitative approach with an explanatory survey design was used in this study. This study involved 360 elementary school students who were selected through probability sampling techniques. Data were collected using a Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that self-efficacy and self-confidence significantly affect learning anxiety. In addition, extrinsic motivation also has a significant influence on learning anxiety. However, the role of extrinsic motivational mediation in the relationship between Self-Efficacy and learning anxiety, as well as between self-confidence and learning anxiety, is not supported by data. The results showed that internal psychological factors played a more prominent role in influencing students' learning anxiety compared to external motivational factors. Therefore, strengthening students' Self-Efficacy and confidence is essential to reduce learning anxiety and encourage a more effective learning experience.